Wallpapering sheet lining with nickel-chromium-molybdenum alloys guidelines. (Nickel Development Institute, 2000)
This document provides guidelines for the procedures employed in wallpapering carbon steel or alloy substrates with high nickel alloys such as UNS N10276 (Alloy C-276). The practices also are applicable to a wide range of lower alloyed nickel-containing materials where appropriate.
Keywords: Metal coating.; Protective coatings.; Protective coverings.; elektronické knihy; electronic books